On nth-order differential operators with Bohr-Neugebauer type property - Aribindi Satyanarayan Rao (International Journal of Mathematics and Mathematical Sciences)
Suppose B is a bounded linear operator in a Banach space. If the differential operator dndtn−B has a Bohr-Neugebauer type property for Bochner almost periodic functions, then, for any Stepanov almost periodic continuous function g(t) and any Stepanov-bounded solution of the differential equation dndtnu(t)−Bu(t)=g(t), u(n−1),…,u′,u are all almost periodic.